Organizational Support, Commitment And Job Satisfaction To Employee Performance - et. al., Dede Hertina, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study is to articulate the direct and indirect effects between perceived organizational support, organizational commitment and job satisfaction on employee performance mediated by organizational citizenship behaviour. Leading theory of this research is social exchange theory followed by the concept of each variable. The research approach in this study is quantitative, with the population of this research is overall Otoritas Jasa Keuangan employees, and the number of representative samples is 317 respondents. Data analysis techniques using path analysis followed by a test such as validity, reliability, normality and hypothesis testing. The results showed that perceived organizational support, organizational commitment and job satisfaction, directly and indirectly, affect employee performance through organizational citizenship behaviour.